Light Stimuli and Circadian Clock Affect Neural Development in Drosophila melanogaster - Dapergola, Eleni; Menegazzi, Pamela; Raabe, Thomas; Hovhanyan, Anna (Frontiers in Cell and Developmental Biology, 2021)
Endogenous clocks enable organisms to adapt cellular processes, physiology and behavior to daily variation in environmental conditions. Metabolic processes in cyanobacteria to humans are under the influence of the circadian clock, and dysregulation of the circadian clock causes metabolic disorders. In mouse and Drosophila, the circadian clock influences translation of factors involved in ribosome biogenesis and synchronizes protein synthesis. Notably, nutrition signals are mediated by the insulin receptor/target of rapamycin (InR/TOR) pathways to regulate cellular metabolism and growth. However, the role of the circadian clock in Drosophila brain development and the potential impact of clock impairment on neural circuit formation and function is less understood. Here we demonstrate that changes in light stimuli or disruption of the molecular circadian clock cause a defect in neural stem cell growth and proliferation. Moreover, we show that disturbed cell growth and proliferation are accompanied by reduced nucleolar size indicative of impaired ribosomal biogenesis. Further, we define that light and clock independently affect the InR/TOR growth regulatory pathway due to the effect on regulators of protein biosynthesis. Altogether, these data suggest that alterations in InR/TOR signaling induced by changes in light conditions or disruption of the molecular clock have an impact on growth and proliferation properties of neural stem cells in the developing Drosophila brain.